Modelling Of PSO - Multilevel Converter To Compensate Unbalanced Voltages (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes a concept of multilevel H-bridge converter based STATCOM to compensate the voltage fluctuations. The control structure of STATCOM is implemented with conventional PI and PSO controllers. The reference signals required for the PSO controller is obtained by dc link voltage of STATCOM. Both the proposals can be controlled to the various objectives such as regulation of voltage,reactive power and harmonic cancellation and unbalanced remuneration. An interesting application for APF based on the PSO can be an increase in the quality of the energy and exposition of the electric train traction power supply system. Pont h based on APF as well as the control strategy they offer is simulated